(untitled) (Pedagogy of Higher and Secondary Education, 2012)
Shklyarova T. P. Problems of modern family and parents’ unpreparedness for gender-role socialization of children. The article analyzes the educational potential of the modern family, and highlights some of the problems faced by modern parents. The areas, which deal with the research of this process, are examined; the analysis of the definitions of gender-role socialization in the scientific literature, such as psychological, sociological and pedagogical, is given.